A Comparison of Optimal Gear Shifts for Stiff and Flexible Driveshafts During Accelerations. Issue 2 (2020) - Ekberg, Kristoffer; Eriksson, Lars
Abstract: Reducing the fuel consumption is important and much development work is on engine optimization for best stationary fuel consumption. Here, a solution is developed for the transient operation to get fuel optimal accelerations, considering the actuation of fuel injection, wastegate control and gear utilization. The transient acceleration scenario studied is; a truck is approaching a red light at slow rolling speed, the light turns green and the truck shall be accelerated to 50 km/h with minimum fuel. Optimal control is used to find the fuel optimal control strategies. By using a dynamic engine model, taking the turbocharger dynamics into consideration, the engine air fuel ratio is taken into account. The differences and similarities between a stiff and flexible driveline model, are analyzed. The results show that the most dominating effect is the turbocharger dynamics of the engine. The two drivelines have similar gear changing strategies while the finer details differ due to the additional degrees of freedom that are present in the flexible driveline.